Mothers' Perceptions Of The Influence Of Environmental Sanitation On The Causes Of Stunting In Toddlers - Annuchasari, Helmi; Azizah, Ninik; Wulandari, Dewi Triloka; Rahmawati, Vivin Eka (Jurnal EduHealth, 2025)
Nutritional status is an important health indicator where the age of toddlers is a group that is very vulnerable to nutritional problems, especially stunting, which is a condition of failure to grow in children under five years of chronic lack of nutrition so that height is less at their age. Research Objectives: to determine the Mother's Perception of the Effect of Environmental Sanitation on the Causes of Stunting in Toddlers. This research is a qualitative research with a case study approach. This research was conducted in the Mayangan Health Center area, Jombang Regency. The informants of this study amounted to 12 consisting of 3 key informants, 8 main informants and 1 supporting informant. Informants were selected by purposive sampling and snowball sampling to obtain the information needed to answer the research questions. The results of the study were that the mother's education level and sanitation were associated with the incidence of stunting, while parental labor and clean water were not associated with the incidence of stunting in Jombang Regency. Environmental sanitation factors are one of the triggers for the emergence of stunting in Jombang District.